Legal aspects of the development of optical medicine for severe systemic diseases - Гетьманцева, Ніна Дмитрівна (м. Чернівці, 2023)
The article is aimed at the development of a new multiparameter polarimetric approach for new methods of Muellermatrix polarization-phase tomography based on the differentiation of polarized and depolarized components and for reproducing the distributions of birefringence value, a set of solutions to the inverse problem - algorithms for polarization reproduction of the distributions of the phase parameters and linear and circular dichroism to determine objective criteria for early diagnosis and differentiation of pathology stages Modern public health is comprehensive in its goal, as it refers to measures aimed at both the entire community and individual health needs. A number of such measures are focused on improving the human environment, reducing risk factors that form a significant burden of disease and mortality among the population and stimulating those factors that, on the contrary, contribute to the promotion and preservation of health
Keywords: new multiparameter polarimetric approach, early diagnosis and differentiation of pathology stages, socioeconomic transformations, statistical monitoring